Supervisi Kepala Sekolah Berbasis Kearifan Lokal dalam Meningkatkan Kinerja Guru pada SD Negeri 7 Simpang Keuramat dan SD Negeri 11 Kutamakmur Kabupaten Aceh Utara - Abubakar (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to (1) analyze the supervision of school principals based on local wisdom to improve teacher performance planning in elementary school; (2) knowing the supervision of school principals based on local wisdom in improving teacher performance in elementary school; (3) analyze the supporting and inhibiting factors of local wisdom-based principal supervision in improving teacher performance in elementary school. The research method used is field research using a multi-site design where the subjects studied have similar backgrounds and institutions with interview, observation, and documentation techniques. This research was carried out at State Elementary School 7 Simpang Keuramat and SD Negeri 11 Kutamakmur. The result of this study is that the implementation of supervision is carried out through three stages, namely supervision planning, supervision implementation and supervision evaluation. The supervision approach used is direct and indirect. The techniques used are two techniques, namely individual techniques which include class visits, class observations, personal meetings, and self-assessment; and group techniques including teacher meetings, discussions, seminars, workshops, and position organizations; has not implemented exchanges, libraries of experiential positions between teachers, panel discussions, and symposiums